Exploring factors causing the high incidence of sexually transmitted infections in the township of Du Noon - Dookhith, Azhaar Bibi Faatimah (Department of Public Health and Family Medicine, 2022)
Introduction: Sexually transmitted infections (STIs) are of major public health concern in South Africa. STIs contribute largely to the burden of disease in South Africa and are recognized as major contributors to the Human Immunodeficiency Virus (HIV) epidemic. Du Noon is a small township situated in Milnerton, Cape Town, South Africa. Du Noon CHC has a large HIV population of approximately 8000 people and recent data obtained from Du Noon CHC statistics, from Nov 2019-Feb 2020 showed 1760 people being treated for STI as per the headcount. Aim: This study intends to explore the factors which may be responsible for the high prevalence of STI among the population of Du Noon Township in Cape Town, South Africa. Methodology: A cross- sectional study with 40 respondents aged between 18 and 45 years was conducted. One-on-one patient interviews using open-ended questions, as well as structured questionnaires, were used to gather data. The questionnaires were analysed using the Likert Scale and open-ended questions were analysed using exploratory descriptive methods. Results: Cultural beliefs, having multiple partners, lack of partner notification, alcohol consumption and lack of condom usage were found to be the main contributing factors to the high incidence of STIs. Sex education at schools appear to be lacking or not in sufficient detail to inform students. The study's findings echoed themes and larger ideas from previous research. It reflects the other well-known cultural and socioeconomic issues confronting South African rural communities e.g., poverty and sex, age -disparate relationships, polygamous relationships. Conclusion: This study fills a gap in the local literature by highlighting how health education challenges, interpersonal relationships, and socioeconomic barriers are still important factors in STI transmission. Although the study's findings may only be applicable to this community, they may have an impact on other communities with comparable populations. The widespread preliminary understanding and framing of HIV as a STI and how it is transmitted needs further investigations and research. As a result, there is an urgent need to shift cultural ideology and norms within the youth of the Du Noon community.